2017
DOI: 10.1155/2017/6354025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Active and Passive Smoking on Retinal Nerve Fibre Layer and Ganglion Cell Complex

Abstract: Aim. To evaluate the possible structural and functional changes in the retinal nerve fibre layer (RNFL) and the ganglion cell complex (GCC) of chronic smokers and compare them with those of passive healthy smokers using spectral domain optical coherence tomography (SD-OCT) and pattern electroretinogram (PERG). Materials and Methods. We include 80 active chronic smokers and 80 age- and sex-matched healthy passive smokers. After a full ophthalmological examination, SD-OCT and PERG were tested for all participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 25 publications
1
6
1
2
Order By: Relevance
“…Potential biologic explanations could be reduced axonal flow or axonal swelling in the course of axonal degeneration due to intake of neurotoxins and cytotoxins from cigarette smoke. However, our results are in contrast with findings of earlier studies 27,28 , which reported reduced pRNFLT in smokers. Suggested mechanisms leading to decreased pRNFLT were toxic damage through free radicals, increased IOP and reduced perfusion [27][28][29] .…”
Section: Discussioncontrasting
confidence: 99%
“…Potential biologic explanations could be reduced axonal flow or axonal swelling in the course of axonal degeneration due to intake of neurotoxins and cytotoxins from cigarette smoke. However, our results are in contrast with findings of earlier studies 27,28 , which reported reduced pRNFLT in smokers. Suggested mechanisms leading to decreased pRNFLT were toxic damage through free radicals, increased IOP and reduced perfusion [27][28][29] .…”
Section: Discussioncontrasting
confidence: 99%
“…23 In the present study, PERG-P50 amplitude and latency did not show significant differences between both groups, while PERG-N95 demonstrated statistically significant differences between the smokers and control groups. These results are comparable to studies by El-Shazly et al, 22 Gűndogân et al 24 and Holder 25 which reported that smoking affects PERG amplitude and latency significantly in heavy smokers compared with non-smokers. We also found significant reduction of phNR amplitude and prolonged latency in heavy smokers compared with control group.PERG-N95 and phNR are objective tests for ganglion cell functions.…”
Section: Figuresupporting
confidence: 90%
“…Although El-Shazly et al 22 concluded that total RNFL and GCC were not significantly influenced when they compared active and passive smokers, the sub-analysis of the quadrants showed that superior and inferior quadrants of RNFL were thinner in the active smokers than passive smokers, with no change in temporal or nasal quadrants. These findings were fairly similar to our results.…”
Section: Figurementioning
confidence: 90%
“…Dizygotic (DZ) twins were pooled with siblings because the genetic sharing within DZ twin pairs is similar to the genetic sharing between siblings, and the number of DZ twin pairs was too small to be separated 19 . While estimating ICCs, age, sex, axial length, presence of diabetes, and hypertension, and smoking history were adjusted as they may influence macular thickness [33][34][35][36][37] .…”
Section: Statistical Analysesmentioning
confidence: 99%